First dinosaur from the Isle of Eigg (Valtos Sandstone Formation, Middle Jurassic), Scotland - Panciroli, E; Funston, GF; Holwerda, F; Maidment, SCR; Foffa, D; Larkin, N; Challands, T; Depolo, PE; Goldberg, D; Humpage, M; Ross, D; Wilkinson, M; et al. (Cambridge University Press, 2020)
Dinosaur body fossil material is rare in Scotland, previously known almost exclusively from the Great Estuarine Group on the Isle of Skye. We report the first unequivocal dinosaur fossil from the Isle of Eigg, belonging to a Bathonian (Middle Jurassic) taxon of uncertain affinity. The limb bone NMS G.2020.10.1 is incomplete, but through a combination of anatomical comparison and osteohistology, we determine it most likely represents a stegosaur fibula. The overall proportions and cross-sectional geometry are similar to the fibulae of thyreophorans. Examination of the bone microstructure reveals a high degree of remodelling and randomly distributed longitudinal canals in the remaining primary cortical bone. This contrasts with the histological signal expected of theropod or sauropod limb bones, but is consistent with previous studies of thyreophorans, specifically stegosaurs. Previous dinosaur material from Skye and broadly contemporaneous sites in England belongs to this group, including Loricatosaurus and Sarcolestes and a number of indeterminate stegosaur specimens. Theropods such as Megalosaurus and sauropods such as Cetiosaurus are also known from these localities. Although we find strong evidence for a stegosaur affinity, diagnostic features are not observed on NMS G.2020.10.1, preventing us from referring it to any known genera. The presence of this large-bodied stegosaur on Eigg adds a significant new datapoint for dinosaur distribution in the Middle Jurassic of Scotland.